Non-gastric advanced mucosa-associated lymphoid tissue (MALT) lymphoma has worse prognosis than gastric MALT lymphoma even when treated with rituximab-containing chemotherapy. Issue 9 (September 2013) - Ueda, Kyoko; Terui, Yasuhito; Yokoyama, Masahiro; Sakajiri, Sakura; Nishimura, Noriko; Tsuyama, Naoko; Takeuchi, Kengo; Hatake, Kiyohiko
Abstract: The aim of this study was to assess the clinical characteristics, treatment results, and analyze the prognostic factors among patients with extranodal marginal zone B-cell lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma). We retrospectively reviewed 98 patients with MALT lymphoma consecutively diagnosed at the Cancer Institute Hospital. Eighty-one patients (82%) had localized disease and 17 patients (17%) had advanced disease. The primary site was gastric in 52, and extra-gastric in 46. With a median follow-up of 40 months, the estimated 3-year overall survival (OS) and progression free survival (PFS) of the entire group were 100% and 89%, respectively. Three-year PFS was significantly better in patients with gastric lymphoma than in those with non-gastric lymphoma (95% vs. 82%, p = 0.043). Patients with localized disease had significantly better 3-year PFS than those with advanced disease (94% vs. 73%, p = 0.026). Upon multivariate analysis, non-gastric lymphoma retained prognostic significance for PFS.